1971
DOI: 10.1128/aem.21.2.165-168.1971
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Metabolism in the Bovine Rumen

Abstract: Rumen microorganisms rapidly metabolize citric acid to carbon dioxide and acetic acid. The rate of metabolism varied between 0.00008 and 0.76 ,moles per g per min, the rate becoming higher as the citric acid concentration increased. The addition of potassium chloride to rumen contents decreased the rate of utilization. The results indicate that dietary citric acid is unlikely to accumulate in the rumen to a sufficiently high level to be an important factor in hypomagnesemia, except where other factors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Later, rumen microflora populations probably adjust to the new diet and decompose the organic acids. An exception to this conditioning occurs in the presence of high K levels, which are known to decrease the rate at which rumen microorganisms can utilize citric acid (14).…”
Section: Resultsmentioning
confidence: 99%
“…Later, rumen microflora populations probably adjust to the new diet and decompose the organic acids. An exception to this conditioning occurs in the presence of high K levels, which are known to decrease the rate at which rumen microorganisms can utilize citric acid (14).…”
Section: Resultsmentioning
confidence: 99%
“…Wright (18) and Kennedy (11) observed that citrate and aconitate, respectively, were rapidly metabolized by rumen bacteria, and they questioned the importance of these organic acids in hypomagnesemia. In our experiments, citrate and aconitate were, likewise, fermented at a rapid rate, and it seemed unlikely that they would be present in the rumen for a long enough time to decrease the availability of dietary magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Scotto et al (1971) noted a positive relation between dietary KCl treatment and citrate absorption, but we did not observe a significant effect of KCl on tricarballylate absorption. Citrate is rapidly fermented by rumen microorganisms (Wright, 1971 ;Russell & Van Soest, 1984); however, KCl may have increased rumen fluid dilution rate and washed citrate out of the rumen before it could be fermented. During the experimental period, sheep given KCl consumed twice as much water but aconitate was never detected in the blood.…”
Section: Fs C U S Si Onmentioning
confidence: 99%